SENAM LANSIA MEMPENGARUHI TEKANAN DARAH LANSIA DI PUSKESMAS KEBONSARI SURABAYA - Nety Mawarda Hatmanti; Diyah Pratiwi (Jurnal Ilmiah Kesehatan, 2013)
Hypertension is the most dominant disease whose cases are increasing to all over the world, happening especially to the elderly. The correct prevention and treatment can decrease Hypertension. One of the non-pharmacological treatments for Hypertension is the physical activity, such as the gymnastics for the elderly. The routine gymnastics will affect on the blood circulation, which will increase the function of heart so that the blood will be pumped to all over the body and finally decrease the blood pressure. The design of research was analytic-cross sectional.The population involved 63 elderly visiting Posyandu (Integrated Health Post) for the elderly in which 40 elderly were taken as the samples by using simple random sampling technique. The data were analyzed by using Chi-square statistic test with the significance level α = 0,05. The result of research showed the significant change on the blood pressure of the elderly who have actively done the gymnastics (ρ < 0,002). This research showed a relationship between the gymnastics for the elderly and the blood pressure of the elderly. In conclusion, the health workers at Puskesmas (Community Health Center) are expected to be more active in conducting the gymnastics for the elderly routinely so that they can get maximum result. Moreover, the community nurses should give information about benefits of gymnastics to the elderly so that they will get motivated to do it routinely.